Microvascular Complications in Type 1 Diabetes: A Comparative Analysis of Patients Treated with Autologous Nonmyeloablative Hematopoietic Stem-Cell Transplantation and Conventional Medical Therapy - Penaforte-Saboia, Jaquellyne G.; Montenegro, Renan M.; Couri, Carlos E.; Batista, Livia A.; Montenegro, Ana Paula D. R.; Fernandes, Virginia O.; Akhtar, Hussain; Negrato, Carlos A.; Malmegrim, Kelen Cristina Ribeiro; Moraes, Daniela Aparecida; Dias, Juliana B. E.; Simões, Belinda P.; et al. (Frontiers in Endocrinology, 2017)
OBJECTIVE: To explore the impact on microvascular complications, long term preservation of residual B-cell function and glycemic control of patients with type 1 diabetes treated with Autologous Nonmyeloablative Hematopoietic Stem Cell Transplantation (AHST) compared to conventional medical therapy (CT). RESEARCH DESIGN AND METHODS: Cross-sectional data of patients treated with AHST were compared with patients who received conventional therapy from the BrazDiab1, the largest multicenter observational study in type 1 diabetes mellitus in Brazil. Both groups of patients had diabetes for 8 years on average. An assessment comparison was made on the presence of microvascular complications, residual function of B-cell, A1c and insulin dose of the patients. RESULTS: ¬After a median of 8 years of diagnosis, none of the AHST-treated patients (n=24) developed microvascular complications while 21.5% (31/144) had at least one (p<0.005) complication in the CT group (n=144). Furthermore, no case of nephropathy was reported in the AHST group while 13.8% of CT group (p<0.005) developed nephropathy during the same period. With regard of residual B-cell function, the percentage of individuals with predicted higher C-peptide levels (IDAA1C ≤ 9) was about tenfold higher in the AHST group compared with CT (75% vs 8.3%) (p<0.001). Among AHST patients, 54.1% (13/24) had the HbA1c<7.0 compared to 13.1% in the CT (p<0.001). CONCLUSIONS: Patients with newly-diagnosed type 1 diabetes treated with AHST presented lower prevalence of microvascular complications, higher residual B-cell function and better glycemic control compared to the CT group. KEYWORDS: type 1 diabetes, autologous nonmyeloablative hematopoietic stem-cell transplantation, residual B-cell function, glycemic control, microvascular complications.